2017
DOI: 10.1038/s41467-017-01046-w
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed Wnt signaling leads to neuronal migration delay, altered interhemispheric connections and impaired social behavior

Abstract: Perturbed neuronal migration and circuit development have been implicated in the pathogenesis of neurodevelopmental diseases; however, the direct steps linking these developmental errors to behavior alterations remain unknown. Here we demonstrate that Wnt/C-Kit signaling is a key regulator of glia-guided radial migration in rat somatosensory cortex. Transient downregulation of Wnt signaling in migrating, callosal projection neurons results in delayed positioning in layer 2/3. Delayed neurons display reduced ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 71 publications
3
50
0
Order By: Relevance
“…DDX3X has been reported to influence canonical Wnt signaling (Cruciat et al, 2013;Snijders Blok et al, 2015), which has known roles in progenitors and migrating neurons during corticogenesis (Bocchi et al, 2017;Harrison-Uy and Pleasure, 2012). Therefore, we examined during these critical phases of brain development.…”
Section: Wnt Signaling Is Not Affected In the Developing Neocortexmentioning
confidence: 99%
“…DDX3X has been reported to influence canonical Wnt signaling (Cruciat et al, 2013;Snijders Blok et al, 2015), which has known roles in progenitors and migrating neurons during corticogenesis (Bocchi et al, 2017;Harrison-Uy and Pleasure, 2012). Therefore, we examined during these critical phases of brain development.…”
Section: Wnt Signaling Is Not Affected In the Developing Neocortexmentioning
confidence: 99%
“…It was shown that NAP could enhance microtubule assembly and neurite outgrowth by interacting with tubulin, and protect neurons and glia exposed to toxins in mouse and rat models 15, 16 . Recently, it was shown that the major symptoms of the Helsmoortel-Van der Aa syndrome, such as developmental delays, vocalization impairments, motor and pace dysfunctions, and social and object memory impediments, could be partially ameliorated by daily NAP administration 17, 18 . We wondered whether NAP alone could be sufficient to interact with β-Catenin.…”
Section: Resultsmentioning
confidence: 99%
“…9b-g). It is well-known that Wnt signaling plays key roles in cell fate determination, differentiation, proliferation and apoptosis 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Wnt proteins are known to play major roles in directing neuronal migration and axondendritic guidance in vertebrates (Bocchi et al, 2017;Yoshikawa et al, 2003). In C.…”
Section: Introductionmentioning
confidence: 99%